Climate Change and Birth Weight - Deschênes, Olivier; Greenstone, Michael; Guryan, Jonathan (American Economic Review, 2009)
There is a growing consensus that emissions of greenhouse gases due to human activity will alter the earth’s climate, most notably by causing temperatures, precipitation levels, and weather variability to increase. The design of optimal climate change mitigation policies requires estimates of the health and other benefits of reductions in greenhouse gases; current evidence on the magnitude of the direct and indirect impacts, however, is considered insufficient for reliable conclusions (A. J. McMichael et al. 2003).